Coordinated Development Strategy for Nuclear Power and New Energy in the Evolution Process of Power System with High Penetration of New Energy - Kuan ZHENG; Zhicheng XU; Gang LU; Fuqiang ZHANG; Junshu FENG; Jinfang ZHANG (Zhongguo dianli)
As important components of non-fossil energy, the nuclear energy and new energy are playing a significant role in constructing the clean, low-carbon, safe and efficient energy system in China. With large scale integration of new energy, the power system is confronted with enormous challenges in safe and stable operation. Nuclear power is stable in output and large in moment of inertia, which can provide necessary power, electricity and inertia support for the power system with high penetration of new energy. For coordinated development of nuclear power, new energy and other power sources in the evolution process of power system with high penetration of new energy, and with consideration of the mutual effects of system planning and operation, this paper establishes a complete set of analytical models based on the mid-long term power planning model (GESP) and the stochastic production simulation model of power system (GridView). It also proposes the reasonable development scale, structure and layout of nuclear power and new energy in China. Considering the influence of nuclear power and other power sources participating in power grid peak regulation with different modes on new energy accommodation and system operation economy, some strategic suggestions are proposed to promote the coordinated operation of nuclear power and new energy, which may provide a decision-making support for promoting orderly and healthy development of nuclear power and new energy, and advancing the energy transformation in China.